SLOVENIAN VERBS OF FALLING: A LEXICO-TYPOLOGICAL ASPECT (Philological Studies, 2019)
Slovenian verbs of falling are considered within frames, which are frequently opposed in various languages. Along with the frames, which are lexicalized in many world languages (falling of multiple objects, collapse etc.), Slovenian also possesses some specific parameters of falling: falling from a great height, falling out of tiredness or clumsiness.
Keywords: Slovenian language, lexical typology, semantics, verbs of falling